New trends in techniques of animation - Pertíñez López, Jesús (Historia y Comunicación Social, 2014)
The current animation is trapped by a film industry that has bet all their creativity to 3D techniques. Overcome the fascination of the first technical advances the future of animation only happens for the revitalization of primitive techniques with current software.
Keywords: animation; primitive techniques; new trends